2022
DOI: 10.3389/fonc.2022.929037
|View full text |Cite
|
Sign up to set email alerts
|

The function and regulatory mechanism of RNA-binding proteins in breast cancer and their future clinical treatment prospects

Abstract: Breast cancer is the most common female malignancy, but the mechanisms regulating gene expression leading to its development are complex. In recent years, as epigenetic research has intensified, RNA-binding proteins (RBPs) have been identified as a class of posttranscriptional regulators that can participate in regulating gene expression through the regulation of RNA stabilization and degradation, intracellular localization, alternative splicing and alternative polyadenylation, and translational control. RBPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 144 publications
0
5
0
Order By: Relevance
“…TA03875 codes for RNA poly(A)-binding protein which is a post-transcriptional regulator of gene expression controlling mRNA stability, polyadenylation, and other functions. An aberrant expression of this gene has previously been reported to be associated with the development of breast cancer 64 , 65 , this gene was down-regulated in attenuated passage in the attenuated Beja passage (log2 Fold Change = − 0.9; p < 0.001). We also found that this gene contains a nucleus localization signal (NLS) which suggest its possible transport into the host nucleus, however this needs to be confirmed since previous studies showed that some genes such as TaMISHIP (T. annulata proline‐rich microtubule and SH3 domain‐interacting protein) presented NLS but they were not detected in the host nucleus 66 .…”
Section: Discussionmentioning
confidence: 82%
“…TA03875 codes for RNA poly(A)-binding protein which is a post-transcriptional regulator of gene expression controlling mRNA stability, polyadenylation, and other functions. An aberrant expression of this gene has previously been reported to be associated with the development of breast cancer 64 , 65 , this gene was down-regulated in attenuated passage in the attenuated Beja passage (log2 Fold Change = − 0.9; p < 0.001). We also found that this gene contains a nucleus localization signal (NLS) which suggest its possible transport into the host nucleus, however this needs to be confirmed since previous studies showed that some genes such as TaMISHIP (T. annulata proline‐rich microtubule and SH3 domain‐interacting protein) presented NLS but they were not detected in the host nucleus 66 .…”
Section: Discussionmentioning
confidence: 82%
“…For example, RBPs can act as cofactors for viral RNA polymerases or helicases, enhancing their activity and promoting efficient viral RNA synthesis [6,7]. Additionally, RBPs may regulate RNA stability and secondary structure, ensuring proper template recognition and efficient replication [8].…”
Section: Role Of Rbps In Viral Replicationmentioning
confidence: 99%
“…During the process of developing therapies, it is necessary to consider the RBP effects in the context of polyQ SCAs, promoting the beneficial ones and reducing those that are harmful, with the final goal of restoring RNA homeostasis (Cornelius et al., 2022). To this end, some potential therapeutic strategies targeting RBPs can encompass gene‐coding delivery (Cornelius et al., 2022) and pharmacological agents (Lu et al., 2022).…”
Section: Rbps As Possible Molecular Targets For Polyq Scasmentioning
confidence: 99%